2012
DOI: 10.1186/1752-4458-6-23
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of depression and associated factors in Ethiopia: findings from the National Health Survey

Abstract: BackgroundIntegrating mental health into primarily health care and studying risk for mental health particularly depression needs assessment of different factors including those that impede diagnosis and treatment of mental disorders. But so far the numbers of literature for local context to analyze risk factors for depression and its treatment are scare. The objective of this study was to assess risk factors and health service attendance for depression among adults, in Ethiopia.MethodsFor this analysis, data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
100
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(118 citation statements)
references
References 27 publications
10
100
8
Order By: Relevance
“…The loss of a spouse has been documented as a predictor of depression in DM patients (Téllez-Zenteno and Cardiel, 2002; Hailemariam et al, 2012). Our findings are in keeping with these previous studies, and could be explained by the fact that loss of a spouse is associated with high levels of stress and could be aetiological in the development of depression.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of a spouse has been documented as a predictor of depression in DM patients (Téllez-Zenteno and Cardiel, 2002; Hailemariam et al, 2012). Our findings are in keeping with these previous studies, and could be explained by the fact that loss of a spouse is associated with high levels of stress and could be aetiological in the development of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Although major depression may develop at any age, the average age of onset is 15 to 19 years in females and 25 to 29 years for males with the average age of onset steadily decreasing over past decades [1,13]. According to study conducted using data from the Canadian National Population Health Survey Being young (aged 12 to 24 years), being divorced, separated, or widowed and having low family income level were positively associated with depression [14].…”
Section: Sample Size Determinationmentioning
confidence: 99%
“…A study using data from 1994 found the lifetime prevalence of MDD in Addis Ababa to be 2.7%, with a 0.2% prevalence of recurrent episodes (Kebede & Alem, 1999a) while the prevalence of suicidal ideation was 2.7% and lifetime prevalence of suicide attempts was 0.9% (Kebede & Alem, 1999b). Collectively, available studies shown that low educational attainment, employment status, female sex, older age, widowed and divorced marital status, self-reported poorer physical and mental health, and substance abuse are risk factors for MDD and suicidal behavior among Ethiopians (Awas et al, 1999; Deyessa et al, 2008; Hailemariam et al, 2012; Kebede & Alem, 1999a; Kebede & Alem, 1999b; Shibre et al, 2014) although most prior studies were conducted in rural settings.…”
Section: Introductionmentioning
confidence: 99%